Characterization of Silica in sandstone rocks for Advanced Energy Applications - ChaaHalima; Krouri,Zohra; Akli,Ouissam; Allam, Djaouida; Mokaddem ,Sarah (University of Eloued جامعة الوادي, 2024)
Silica (SiO2), represents a main component used in various applications such as the manufacture of photovoltaic cells and fiberglass. Despite this importance, the use of silica in Algeria remains limited due to the quality of the material or unknown for some deposit. In this work, we carried out an in-depth characterization of the siliceous sandstone samples, using various advanced qualitative and quantitative characterization techniques of metallographic microscope, granulometric analysis, DRX and XRF. The results showed that the different characterized samples have a fairly silicon dioxide (SiO2) purity of 89.15 % at 250-400 μm of size with the presence of different types of defects, namely mineral inclusions of clay and oxide minerals. The presence of impurities, in particular iron and aluminum, limit the use of this silica for the production of advanced materials
Article
Keywords: Silica; sandstone; characterization; photovoltaic; energy